Serum B-cell maturation antigen could be a simple and accurate biomarker to identify and prognosticate monoclonal gammopathy of undetermined significance and smoldering multiple myeloma - Masanori Toho; Daisuke Ikeda; Shuichi Aikawa; Chiho Misono; Mitsuaki Oura; Fuminari Fujii; Hajime Sakuma; Atsushi Uehara; R ikako Tabata; Kentaro Narita; Masami Takeuchi; Tomohisa Watari; et al. (Haematologica)
Not available.